INTERNATIONAL ADOPTION: REALITY AND CHALLENGES - Kukhianidze, Ketevan (European Scientific Journal, ESJ, 2014)
The presented work is about one of the important issues of child adoption institute - international adoption. The main objective of the article is to discuss specific issues related to international adoption and to promote the role of Georgia in protection of children’s rights. With the help of the research methods of comparative and logical analysis, the Georgian legislation "On Adoption and Foster Care" as well as different legal acts and statistical database of international adoption existing in Georgia nowadays will be realized.